Ground plane impact on quadrifilar helix antenna performance with respect to deployment heights. (19th July 2019) - Ahmad, Muhammad; Khan, Asim Ali; Amin, Muhammad; Asif, Hafiz M.; Baig, Sobia
Summary: Quadrifilar helix antenna (QHA) has its applications in satellite communications. This paper presents the performance optimisation of input and radiation characteristics of QHA in the presence of infinite and finite metallic ground planes. For the infinite ground plane, it has been observed that input parameters such as impedance and voltage standing wave ratio (VSWR) are stable, and the antenna has broader half power beamwidth (HPBW). Smaller metallic platforms that act as finite ground planes produce better 3‐dB axial ratio beamwidth and boresight axial ratio. Deployment of QHA on smaller metallic platforms such as nanosatellites and CubeSats enhances the circularly polarised beamwidth of the antenna with improved boresight axial ratio. However, on large low earth orbit (LEO) satellites, stable input characteristics and broader HPBW have been achieved at the cost of narrow circularly polarised beamwidth and degraded boresight axial ratio. Abstract : This paper presents the performance optimisation of input and radiation characteristics of QHA in the presence of infinite and finite metallic ground planes. It has shown that smaller metallic platforms that act as finite ground planes produce better 3‐dB axial ratio beamwidth and boresight axial ratio. Other performance parameters including impedance, voltage standing wave ratio (VSWR), and half power beamwidth (HPBW) have been measured.